Bacterial degradation of chlorophenols and their derivatives - Arora, Pankaj Kumar (BioMed Central, 2014)
Chlorophenols (CPs) and their derivatives are persistent environmental pollutants which are used in the manufacture of dyes, drugs, pesticides and other industrial products. CPs, which include monochlorophenols, polychlorophenols, chloronitrophenols, chloroaminophenols and chloromethylphenols, are highly toxic to living beings due to their carcinogenic, mutagenic and cytotoxic properties. Several physico-chemical and biological methods have been used for removal of CPs from the environment. Bacterial degradation has been considered a cost-effective and eco-friendly method of removing CPs from the environment. Several bacteria that use CPs as their sole carbon and energy sources have been isolated and characterized. Additionally, the metabolic pathways for degradation of CPs have been studied in bacteria and the genes and enzymes involved in the degradation of various CPs have been identified and characterized. This review describes the biochemical and genetic basis of the degradation of CPs and their derivatives.